Multidimensional trophic niche revealed by complementary approaches: Gut content, digestive enzymes, fatty acids and stable isotopes in Collembola. Issue 8 (31st May 2021) - Potapov, Anton M.; Pollierer, Melanie M.; Salmon, Sandrine; Šustr, Vladimír; Chen, Ting‐Wen
Abstract: Trophic niche differentiation may explain coexistence and shape functional roles of species. In complex natural food webs, however, trophic niche parameters depicted by single and isolated methods may simplify the multidimensional nature of consumer trophic niches, which includes feeding processes such as food choice, ingestion, digestion, assimilation and retention. Here we explore the correlation and complementarity of trophic niche parameters tackled by four complementary methodological approaches, that is, visual gut content, digestive enzyme, fatty acid and stable isotope analyses—each assessing one or few feeding processes, and demonstrate the power of method combination. Focusing on soil ecosystems, where many omnivore species with cryptic feeding habits coexist, we chose Collembola as an example. We compiled 15 key trophic niche parameters for 125 species from 40 studies. We assessed correlations among trophic niche parameters and described variation of these parameters in different Collembola species, families and across life‐forms, which represent microhabitat specialisation. Correlation between trophic niche parameters was weak in 45 out of 64 pairwise comparisons, pointing at complementarity of the four methods. Jointly, the results indicated that fungal‐ and plant‐feeding Collembola assimilate storage, rather than structural polysaccharides, and suggested bacterial feeding as a potential alternative feeding strategy. Gut content and fatty acid analyses suggested alignment between ingestion and assimilation/retention processes in fungal‐ and plant‐feeding Collembola. From the 15 trophic niche parameters, six were related to Collembola family identity, suggesting that not all trophic niche dimensions are phylogenetically structured. Only three parameters were related to the life‐forms, suggesting that species use various feeding strategies when living in the same microenvironments. Consumers can meet their nutritional needs by varying their food choices, ingestion and digestion strategies, with the connection among different feeding processes being dependent on the consumed resource and consumer adaptations. Multiple methods reveal different dimensions, together drawing a comprehensive picture of the trophic niche. Future studies applying the multidimensional trophic niche approach will allow us to trace trophic complexity and reveal niche partitioning of omnivorous species and their functional roles, especially in cryptic environments such as soils, caves, deep ocean or benthic ecosystems. Abstract : The authors revealed the information provided by four complementary methods in trophic ecology, including visual gut content‐, digestive enzyme‐, fatty acid‐ and stable isotope analyses, thereby to demonstrate multidimensional nature of trophic niches in Collembola—one of the functionally diverse taxa with cryptic feeding habits in soil.